"Devil Tools & Tech": A Synergy of Conservation Research and Management Practice. Issue 1 (4th January 2016) - Hogg, Carolyn J.; Grueber, Catherine E.; Pemberton, David; Fox, Samantha; Lee, Andrew V.; Ivy, Jamie A.; Belov, Katherine
Abstract: Biodiversity conservation continually presents new challenges, yet conservation resources are limited, and funding for applied conservation research projects more so. Recently, many have reported on the "research–implementation gap, " whereby conservation research findings are infrequently translated into conservation actions. In this perspective, we describe our experiences working in a large multi‐institutional, multi‐disciplinary team as we attempt to bridge the research–implementation gap by developing conservation tools needed to address the conservation challenges faced by Tasmanian devils ( Sarcophilus harrisii ). We discuss our project's history, lessons learnt, outcomes, and future plans to provide insights that may help others develop multi‐institutional projects, designed to target rapid and direct implementation of conservation research into management action. Key to our success is the needs‐based prioritization of research measured against the management team's questions, recognition of the different needs of academia, industry and government, a collegiate approach, and willingness to embrace adaptive management. Challenges include developing a project which meets all strategic targets of different institutions, in addition to sourcing funds. Overall, our goal has been to establish an enduring research‐management framework, to facilitate improved integration of scientific research into the management needs of Tasmanian devil conservation, and serve as a template for other species management projects.